2003
DOI: 10.1038/nature01454
|View full text |Cite
|
Sign up to set email alerts
|

Insight into a natural Diels–Alder reaction from the structure of macrophomate synthase

Abstract: The Diels-Alder reaction, which forms a six-membered ring from an alkene (dienophile) and a 1,3-diene, is synthetically very useful for construction of cyclic products with high regio- and stereoselectivity under mild conditions. It has been applied to the synthesis of complex pharmaceutical and biologically active compounds. Although evidence on natural Diels-Alderases has been accumulated in the biosynthesis of secondary metabolites, there has been no report on the structural details of the natural Diels-Ald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
176
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(180 citation statements)
references
References 27 publications
1
176
1
2
Order By: Relevance
“…As such, surface ligands on noble metal nanocatalysts may provide a similar orientation effect to improve the product selectivity through molecule recognition and/or specific regulation on adsorption. One straightforward way is to utilize the structural and chemical similarity of reactants and ligands that potentially can orient reactants through an enthalpy-driven path [45][46][47].…”
Section: Orientation Effect Of Surface Ligandsmentioning
confidence: 99%
“…As such, surface ligands on noble metal nanocatalysts may provide a similar orientation effect to improve the product selectivity through molecule recognition and/or specific regulation on adsorption. One straightforward way is to utilize the structural and chemical similarity of reactants and ligands that potentially can orient reactants through an enthalpy-driven path [45][46][47].…”
Section: Orientation Effect Of Surface Ligandsmentioning
confidence: 99%
“…Major differences, however, lie in the use of a bound Mg 2+ cation, which directly coordinates to the carbonyl oxygens of the dienophile and participates in the catalytic mechanism, and in the generally lower importance of stacking in enzyme-substrate interactions 42,43 .…”
Section: Comparison With Protein-catalyzed Reactionsmentioning
confidence: 99%
“…[13] This reaction type is of great relevance in organic chemistry, [14] and candidates for catalyzing the Diels-Alder reaction in nature are currently under intensive investigation. [15][16][17] This ribozyme was the first RNA enzyme to catalyze a bond-forming reaction enantioselectively, [18] and substrate-specificity studies suggested a simple and convincing structural model for the stereoselectivity (Figure 1b). [19] The size of the diene's substituent was identified as the major determinant of stereoselectivity (see the table in Figure 1), and the diene was thought to enter the catalytic pocket with the sterically less demanding edge first, then react with the maleimide bound in one fixed orientation (Figure 1b, left model), while the opposite orientation of the anthracene (right model) was found to be disfavored.…”
mentioning
confidence: 98%